INTEGRATED ECONOMIC STRATEGIC DEVELOPMENT: TRANSFORMATION FOR SUSTAINABLE GROWTH - Iwan Harsono (CV. Adiba Aisha Amira, 2025)
This research delves into the intricacies of integrated economic, strategic development, seeking to provide a roadmap for nations navigating the complexities of the contemporary global economic landscape. Through a mixed- methods approach encompassing qualitative and quantitative analyses, the study identifies critical challenges, ranging from economic downturns to geopolitical uncertainties, while concurrently illuminating opportunities inherent within these challenges. Successful case studies and global lessons are examined to distill insights into effective economic development strategies, emphasizing the need for context-specific approaches. Strategic planning emerges as a critical component, calling for establishing clear short-term and long-term goals and formulating adaptive implementation strategies. A robust mechanism for measurement and evaluation, encompassing success criteria and performance metrics, is proposed. The findings underscore governments' need to adopt proactive policies that foster innovation, technological advancements, and sustainability. The private sector is urged to embrace adaptability and collaboration, while society benefits from inclusive policies prioritizing education and social safety nets.